Un vuelo sin destino: el Nuevo Aeropuerto Internacional de la Ciudad de México - Soto Coloballes, Natalia Verónica (El Colegio de México A.C., 2023)
The present text describes the different projects and actions carried out during the last twenty years, with the purpose of constructing an airport terminal at the Federal Zone of Lake Texcoco. The analysis outlines two broad positions in this regard, one reassured on the benefits of its edification and the second one as its opposite. Observing both positions draws out the attention to the land and the soil considered, for its relevance and the transformation it has endured, and the natural resources at stake on it.